Gross and fine motor skills in children treated for acute lymphoblastic leukaemia. (June 2013) - De Luca, Cinzia R.; McCarthy, Maria; Galvin, Jane; Green, Jessica L.; Murphy, Alexandra; Knight, Sarah; Williams, Jacqueline
<x xml:space="preserve">Abstract</x> Objective: Chemotherapy treatment for acute lymphoblastic leukaemia (ALL) may disrupt motor development, with suggestions that gross and fine motor deficits are different depending on time since treatment. Methods: Thirty-seven participants aged between 2.5 to 5 years at the time of diagnosis were assessed using the Movement Assessment Battery for Children, 2nd Edition (MABC-2) and the Bruininks–Oseretsky Test of Motor Proficiency, 2nd Edition, Short Form (BOT-2 SF), and divided into groups (i.e. months-off-treatment): (1) 0–12, (2) 13–24, and (3) 25–60 for comparison. Results: MABC-2 and BOT-2 SF mean total scores fell within the average range. Twenty-six percent of the sample performed in the impaired range on the MABC-2. Group 2 had significantly lower Manual Dexterity scores than the normative population and lower BOT-2 SF scores than Group 1. Conclusion: Most children treated for ALL display appropriate motor skills, yet around a quarter experience general motor difficulties. Time-off-treatment did not affect the prevalence of motor impairments on any measure.